Protective effect of picolinic acid on mice intracerebrally infected with lethal doses of Candida albicans. - Blasi, E (1993)
We have studied the effects of picolinic acid (PLA), a product of tryptophan degradation, on mouse susceptibility to intracerebral infection with Candida albicans. We show that intraperitoneal administration of PLA significantly enhances the median survival time of mice inoculated with the lethal challenge. Furthermore, intracerebral administration of this agent induces a protective state against the local lethal infection, the phenomenon depending upon the administration schedule and doses of PLA employed. According to survival data, yeast growth in the brain as well as yeast colonization of the kidneys are drastically reduced in PLA-treated mice compared with those for untreated controls. Northern (RNA) blot analysis of brain tissues demonstrates that mRNA levels specific for tumor necrosis factor and interleukin 1 are augmented and induced, respectively, after inoculation of PLA. These results indicate that PLA has a protective effect likely involving elicitation of a cytokine response in vivo against fungal infections.